Director's Report of Research in Kansas, 2015 - J. E. Minton (Kansas Agricultural Experiment Station Research Reports, 2016)
The 2015 Director’s Report of Research in Kansas includes a list of journal articles, station publications, and other published manuscripts from scientists in our departments, research stations, and associated programs.
Keywords: Agriculture